PENGARUH ASET TIDAK BERWUJUD DAN BIAYA PENELITIAN DAN PENGEMBANGAN TERHADAP NILAI PASAR DAN KINERJA KEUANGAN PERUSAHAAN - Trisnajuna, Made; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
The purpose of this research is to test the influence of intangible asset value and research & development expenditure on corporate market value and financial performance of manufacturing companies which were listed on Indonesia Stock Exchange (IDX) during 2010-2013. Samples were determined using purposive sampling method and consisting of 40 companies with 155 observations. The data in this study was collected through non-partisipan observation method by downloading data from IDX. The testing of hypotheses in this research used multiple linear regression. The result shows that intangible assets value and research & development expenditure influence positively and significantly on corporate market value and financial performance.
Keywords: intangible asset, research and development, corporate market value, financial performance